2020
DOI: 10.1002/brb3.1591
|View full text |Cite
|
Sign up to set email alerts
|

Pregenual or subgenual anterior cingulate cortex as potential effective region for brain stimulation of depression

Abstract: Background:The dorsolateral prefrontal cortex (DLPFC) is the standard stimulation target for the repetitive transcranial magnetic stimulation (rTMS) treatment of major depression disorder (MDD). A retrospective study by Fox and colleagues found that a more negative resting-state functional magnetic resonance imaging (RS-fMRI) functional connectivity (FC) between left DLPFC and the subgenual anterior cingulate cortex (sgACC) in a large group of healthy participants is associated with a better curative effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…The effective connectivity of the fronto-limbic circuit has been suggested as a predictor of response to antidepressants [46]. Most recent study suggests that stimulation of pre-or subgenual ACC might be an effective treatment for depression [47]. Our results of less activation of the abovementioned regions in depressed patients are in line with the cited literature.…”
Section: Discussionsupporting
confidence: 91%
“…The effective connectivity of the fronto-limbic circuit has been suggested as a predictor of response to antidepressants [46]. Most recent study suggests that stimulation of pre-or subgenual ACC might be an effective treatment for depression [47]. Our results of less activation of the abovementioned regions in depressed patients are in line with the cited literature.…”
Section: Discussionsupporting
confidence: 91%
“…DLPFC is a part of the Default Mode Network (DMN), which has been reported to have aberrant function in both OCD and MDD [7,8]. The therapeutic benefit of DLPFC stimulation may be mediated through connections to the subgenual [9] and pregenual [10] anterior cingulate cortex. Interestingly, in Tadayonnejad et al (2018) study, pregenual anterior cingulate cortex was shown to mediate the abnormal interaction between cortico-striatal-thalamo-cortical OCD and frontolimbic MDD circuits.…”
mentioning
confidence: 99%
“…The ACC has been proposed to play a central role in MDD pathology [4951]. While the subgenual part of the ACC is most often highlighted, the pregenual ACC, where our seed was located, has also been found to be part of the altered DMN in MDD and associated with treatment effects [52, 53]. Our finding that ACC connectivity with regions from both other networks differentiates patients with different treatment outcomes further supports this idea and highlights the potential of this feature for predicting early remission in response to pharmacotherapy.…”
Section: Discussionmentioning
confidence: 99%